(Re)considering Haugen's model in the teaching and learning of standard Kiswahili in Uganda. Issue 2 (4th May 2022) - Jjingo, Caesar; Iddi, Zainab Ali
Abstract : In Uganda, Kiswahili is a foreign language and is provided for as the second official language of the country mainly due to its growing importance in the region. While such an official status has significantly increased its teaching in post-primary phases across the country, the question on which Kiswahili variety or varieties to be considered in schools has remained predominantly undecided. As a result, given that the existing language-in-education policy is silent on this matter, the widespread use of various Kiswahili varieties has unceasingly and gradually flourished in the learning institutions of Uganda. This practice contrasts with Kaplan's and Baldauf Jr.'s perspectives on schools, as formal sites for the teaching of a selected or standard variety of a given language. Employing Bowen's document analysis techniques, this article primarily reviews postulations on the teaching of Kiswahili, as primarily outlined in the Uganda's existing language-in-education policy. The review offers justifications to explore Haugen's revised language planning model to purposely establish possibilities for (re-)emphasising the teaching and learning of standard Kiswahili in the Uganda's education systems.